Determining the Offshore Wind Power Potential in the Mix-electric Power of Vietnam: The Role of Feed-in Tariff Policy - Bui, Xuan Hoi; Nguyen, Phuong Thao (International Journal of Energy Economics and Policy, 2022)
The purpose of the research is to examine the offshore wind power potential in the mix-electric power of Vietnam. By using net present value method, the paper also aims to explore how economic factors influence the offshore wind power feasibility in the conditions that the technical factors are ensured. The result indicates that offshore wind power will have a low proportion in the mix-electric power of Vietnam before 2030 and may be accelerated in the period 2035 – 2040. Electricity supply from offshore wind is not economically viable without improvements in investment, operating costs, and capacity factor. In particular, the Feed-in-Tariff (FIT) policy designed to support the development of renewable energy sources by providing a guaranteed, above-market price for producers, will be a decisive factor in developing offshore wind power of Vietnam. Additionally, the differences between characteristics of site's condition leading to the disparities in capital and operational expenditure and capacity factor. Thus, the electricity price and the subsidies for bottom-fixed sites and floating sites should be disparate and the location of offshore wind farms should be considered to ensure the harmonization of the profits derived from different types of offshore wind farms.